(untitled) - Svrcek, William Y. (Chichester, West Sussex, United Kingdom, 2014)
Building on the success of the previous editions, this new third edition of A Real-Time Approach to Process Control employs both real industry practice and process control education without the use of complex or highly mathematical techniques, providing a more practical and applied approach
Keywords: Process control,Real-time control,Kiểm soát tiến trình; Data processing,Xử lý dữ liệu